PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 022 RTP. KIRI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Ridani '; Damanhuri Daud Damanhuri Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem this research is the students achievement of IPA fourth graderst studies still low with an average value of 59,3 and minimum completeness criteria (KKM) IPA studies is 65. Between students, amounting to 22 people only 9 students who achieve classical KKM with 41%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of IPA studies class IV at SDN 022 Rantau Panjang Kiri with implementation cooperative learning model with tipes TPS. Formulation of the problem: is the implementation of cooperative learning model with tipes TPS can improve students achievement of IPA studies at SDN 022 Rantau Panjang Kiri. Subjects were students of SDN 022 Rantau Panjang Kiri, totaling 22 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 59,3. In the first cycle improve an average of 69,5 and an improved in the second with an average of 78,8. Results in the class IV at SDN 022 Rantau Panjang Kiri that the implementation of cooperative learning model with tipes TPS can improved the student achievement of IPA studies at fourth graders SDN 022 Rantau Panjang Kiri. Key words: Cooperative Type Think Pair Share, the result of IPA